Faith-Based Ecological Counselling: Integrating Spirituality and Sustainability for Muslim Students - Hidayat, Hidayat; Pendi, Hamdi Zas; Warlizasusi, Jumira (Studia Ecologiae et Bioethicae, 2026)
The global ecological crisis demands transformative innovations in Islamic higher education to cultivate environmentally responsible behaviours grounded in spiritual values. This study explores a faith-based ecological counselling model that integrates Islamic spirituality with sustainable behaviour change among Muslim students. Employing a qualitative design with a phenomenological approach and multiple case studies at Sultan Thaha Saifuddin State Islamic University of Jambi and Maulana Malik Ibrahim State Islamic University of Malang, data were collected through in-depth interviews, participatory observations, reflective eco-journals, and focus group discussions (FGDs), and analysed using thematic analysis with NVivo. Findings reveal that interventions such as Green Reflection Circles, Spiritual Eco-Walks, and Eco-Journal Counselling effectively fostered spiritual-ecological values in students’ beliefs and actions. Behavioural transformation was observed across cognitive (enhanced ecological literacy), affective (strengthened empathy toward nature), and practical (eco-friendly lifestyle practices) domains. Nevertheless, challenges emerged, including pedagogical gaps and limited institutional support for mainstreaming sustainability education in campus settings. This research contributes to the theoretical development of Islamic counselling for sustainability and recommends structured counsellor training and curriculum integration for ecological literacy and action. Future directions include designing quantitative instruments, expanding research contexts, and adopting longitudinal approaches. The study aligns with SDG 4 (Quality Education), SDG 12 (Responsible Consumption), and SDG 13 (Climate Action), while reinforcing Green Campus initiatives within Islamic higher education institutions.